Safely and effectively reducing inpatient length of stay: a controlled study of the General Internal Medicine Care Transformation Initiative. Issue 6 (9th October 2013) - McAlister, Finlay A; Bakal, Jeffrey A; Majumdar, Sumit R; Dean, Stafford; Padwal, Rajdeep S; Kassam, Narmin; Bacchus, Maria; Colbourne, Ann
Abstract : Purpose: Whether improving the efficiency of hospital care will worsen post-discharge outcomes is unclear. We designed this study to evaluate the General Internal Medicine (GIM) Care Transformation Initiative implemented at one of the seven teaching hospitals in the Canadian province of Alberta. Methods: Controlled before–after study of GIM patients hospitalised at the University of Alberta Hospital (UAH, intervention site, n=1896) or the six other teaching hospitals in Alberta—three in Edmonton (intra-regional controls (IRC), n=4550) and three in Calgary (extra-regional controls (ERC), n=4095). The primary effectiveness outcome was risk-adjusted length of stay (LOS) and the primary safety outcome was 'mortality during index hospitalisation or all-cause readmission or death within 30-days of discharge'. Results: LOS for GIM patients decreased by 0.68 days at Alberta teaching hospitals between 2009 and 2012; GIM patients hospitalised at the UAH exhibited a further 20% relative decline in adjusted LOS (total reduction=1.43 days, 95% CI 0.94 to 1.92 days) from PRE to POST. Interrupted time series (ITS) confirmed that the 1.43 day reduction at the UAH was statistically significant (level change p=0.003), while the declines at the IRC (p=0.37) and ERC (p=0.45) were not. Our safety outcome did not change for UAH patients (18.4% PRE-intervention vs 17.8% POST-intervention, adjusted OR 1.02 (95%CI 0.80 to 1.31), p=0.42 on ITS), nor for those hospitalised at the IRC (p=0.33) or the ERC (p=0.73) sites. Conclusions: The Care Transformation Initiative was associated with substantial reductions in LOS without increasing post-discharge events commonly quoted as proxies for quality.